Relevansi Takwim Uhadi Dengan Syarat-Syarat Ditetapkan Kongres Istanbul 2016 Bagi Takwim Hijri Global: Relevance of Uhadi Calendar with Conditions Determined by Istanbul Congress 2016 For Global Hijri Calendar - Rodzali, Muhamad Zakuwa; Man, Sa’adan (Online Journal of Research in Islamic Studies, 2021)
The early celebration of Ramadan, Aidilfitri and Aidiladha among the Muslim world which sometimes varies to several days has revived suggestions on the need for a global hijri calendar. Accordingly, at the Kongres Penyatuan Kalendar Hijri Seluruh Dunia in Istanbul, Turkey on 28 to 30 May 2016 a resolution was agreed that the global hijri calendar to be adopted must meet two conditions; the new month should not begin if the hilal is yet unborn and the new month is not delayed if the hilal is clearly visible. In the congress, the Uhadi Calendar was agreed to be adopted as a global hijri calendar. Thus, an analysis of the data of the position of the moon on the 29th day of the lunar month for the period of 20 years from 1437H/2016M till 1457H/2035M is made in confirming the extent to which the Uhadi Calendar fulfills the two conditions that have been agreed in the congress. The results of the analysis found that the Uhadi Calendar itself did not meet the conditions set by the Istanbul Congress. The results of the analysis also found that the criteria of 3˚ the altitude of the moon and 6˚ the elongation of the moon to the sun are more suitable to be used to prepare the global hijri calendar as it is more in line with the current hilal sighting record.